Future of South Korea–Japan Relations: Decoupling or Liberal Discourse. Issue 2 (21st November 2019) - Phillips, Joe; Lee, Wondong; Yi, Joseph
Abstract: South Korea–Japan relations are at their lowest point in decades, as colonial era disputes flare once again. Most pundits argue that the South Korean public is strongly united against Japan. We argue that South Korean elites are sharply divided over how to manage the crisis; this division is starting to impact how South Koreans understand colonial era narratives; and, long‐term, bilateral relations depend on how these growing divisions play out. Despite state censorship, a rising counter‐narrative in South Korea challenges the dominant, Manichaean, anti‐Japanese one. For the first time, Korea and Japan have a realistic chance of reconciling based on liberal public discourse and a nuanced, empirically based understanding of history.